Yesus, Sang Orang Asing: Alternatif Kristologi bagi Orang Indonesia-Tionghoa-Kristen - Kartika Diredja (Asosiasi Teolog Indonesia, 2014)
This article offers one of the alternative solutions for the struggle of the Christian-Chinese-Indonesians in facing their status as strangers in Indonesia. This status is a result of the ongoing stereotyping process which position them as a homogenous group. While in reality, their understandings of their identity in Indonesia are varied. This heterogeneity can be seen through the various alternative solution they made to face the situation. This article gives the alternative solution according to the Christian faith by understanding Jesus Christ’s status as The Stranger. The Gospels show us that Jesus chose His status as The Stranger by purpose to give meaning to it and to use it positively. For Jesus, His status as The Stranger is not a terrible thing, but rather an opportunity to work for His society. His viewpoint to His status can be the viewpoint of Chinese-Indonesians to their status. By that, they can use their status to make their presence relevant in Indonesia.